Pembangunan Sistem Operasi Berbasis Linux Menggunakan Metode Linux From Scratch - Wamiliana Wamiliana; Fahmi Kharismaldie; Wisnu Wardhana (Universitas Lampung, 2013)
GNU/Linux is an operating system that allows the users to build or develop their own operating system. There are two methods that can be used, Remaster and Linux From Scratch. The difference is the LFS method builds a system from zero while Remaster using existing Linux distributions [4]. The goal of this research is to investigate the steps of building Linux base operating system using LFS method. The operating system has been built successfully and can be used to fulfill the daily needs such as playing music or video, browsing, programming, and other tasks.Keywords: GNU/Linux, Linux From Scratch, open source, operating system